Tapping movements according to regular and irregular visual timing signals investigated with fMRI - Lutz, K; Specht, K; Shah, N J; Jäncke, L (Neuroreport, 2000)
Whole-head functional MR images were acquired while 10 subjects were asked to tap with their right index finger in synchrony with a visual stimulus appearing regularly with a frequency of 1.5 Hz, or irregularly with a mean frequency of 1.5 Hz. Performance data show that during regular tapping most taps were close to stimulus onset. However, when the subjects paced their tapping according to the irregular stimuli, most taps appeared about 300 ms after the onset of the pacing stimuli. Comparing the brain activations resulting from regular tapping with those from irregular tapping, we found increased activation in left precuneus only. Comparing irregular versus regular tapping shows increased activity in right cerebellar nuclei and vermis, left ventrolateral thalamus, left sensorimotor cortex, left and right pre-SMA and left SMA proper. These results show that during irregular pacing the motor areas are more strongly activated than during regular pacing. In addition, further neural systems are involved in the motor control during irregular pacing: cerebellar vermis and a cerebello-thalamo-cortical system. The latter is supposedly involved in error correction in the context of visually guided movements.